Pattern of Valvular Involvement in Rheumatic Heart Disease Patients in a Tertiary Care Hospital of Western Nepal - Kafle, Ram Chandra; Alurkar, Vijay Madhab; Paudel, Navaraj; Jha, Girija Shankar (Nepalese Heart Journal, 2016)
Background and Amis: Rheumatic Heart Disease (RHD) is among the commonest diseases of young adults in low-income countries like Nepal. Mitral and aortic valves are more commonly affected than others in RHD. Echocardiography is simple and cost effective tool to identify the patterns of valvular involvement that helps in diagnosis and determines the timing of surgery. This study aimed at determining the pattern of RHD in patients who underwent Echocardiography in a tertiary care hospital of western Nepal. Methods: A retrospective analysis of trans-thoracic echocardiographic record of patients from January 2009 to December 2015 was done. Data were collected in a pre-structured proforma and analyzed. Results: Among 12567 echocardiography, 609 (4.84%) were recorded to have RHD including post valve replacement patients. Females predominated with male to female ratio of 1:2.8. Most patients, 308 (50%) belonged to age group of 21-40 years. The commonest isolated lesion was mitral regurgitation (MR) in 119 (26.21%) patients followed by mitral stenosis (MS) in 31(6.82%) patients. The commonest mixed lesion was MS with MR and aortic regurgitation (AR) seen in 99 (21.8%). The frequency of atrial fibrillation (AF) and stroke was 18% and 3% respectively in RHD patients Conclusions: The proportion of RHD was high in our study. Majority of RHD patients were females of reproductive age group. The commonest lesion was MR followed by mixed valvular lesions. Nepalese Heart Journal 2016; 13(2): 29-31